G189(P) Development of an annual endoscopy audit plan using measures in the P-GRS(paediatric global rating scale for endoscopy) in a tertiary paediatric endoscopy service to facilitate quality improvement. (24th May 2017) - Wan, JWY; Thomson, M; Campbell, D; Belsha, D; Urs, A; Rao, P; Narula, P
Abstract : Background: A paediatric global ratings scale for endoscopy(PGRS) is currently being piloted nationally, and this will provide a quality and safety framework for service improvement in Paediatric endoscopy units. An annual endoscopy audit plan is essential to help units identify that they are meeting the required measures and identifying areas of improvement. Aim: To develop an annual endoscopy audit plan to facilitate quality improvement in the endoscopy service in a tertiary centre. Subjects and Methods: A retrospective audit of all procedures done by the Paediatric gastroenterology team during 1/10/16–15/ 10/16 was done. We used measures from the P-GRS to develop standards for the audit plan. Letters of correspondence, consent, operation notes, anaesthetic charts, nursing documentation and biopsy reports were reviewed. Patient feedback questionnaires were also included. Results: 46 patients(age range 8 months to 17 years) had endoscopies during the study period. 78%(36) of these had elective procedures. Out of the 22%(10) who had non-elective procedures, 18%(8) were urgent and 4%(2) were emergency procedures. 100% of procedures had a clearly documented indication, and had completed consent forms, all of which were 2-stage. The procedure completion rate was 100%, and bowel preparation was adequate in 98%. One patient developed post-operative oxygen requirement; otherwise there were no other post-procedure complications. There were no deaths within 30 days of the procedure. Patient feedback questionnaires showed 78% of respondents rated their overall endoscopy experience as 'excellent' or 'good'. One patient had an endoscopic assessment for Upper GI bleeding during the audit period. This patient was risk assessed and had an endoscopic assessment appropriately. Summary and conclusion: The audit showed that our Unit is performing well against a number of the quality and safety measures in the P-GRS. Areas that require improvement include developing procedure-specific after care patient information leaflets, better documentation on patients' anaesthetic needs, and procuring an endoscopy reporting system(ERS). This also highlighted the need for close collaboration with other stakeholders such as anaesthetics and theatre admissions staff to share findings and implement change.